Vocational education and training attrition and the school-to-work transition - Masdonati, Jonas [Verfasser]; Lamamra, Nadia [Verfasser]; Jordan, Marine [Verfasser] (My University, 2010)
"The purpose of this paper is to explore the issue of dual vocational education and training (VET) attritions as indicating difficulties in the transition from school to work. The purpose of this paper is to explore the issue of dual vocational education and training (VET) attritions as indicating difficulties in the transition from school to work. The findings showed that VET 'dropouts' experience transitional problems. These can be one of two sorts: diachronic or synchronic. Diachronic problems are related to difficulties with the shift from a standard school system to VET. Synchronic problems are due to difficulties in learning, relational or working environments." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; P 2.3 Auszubildende; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); G 1.3.2.2.3 Zweite Schwelle, in Arbeit; I 2.2.1 Westeuropa; Berufsbildungssystem; Duales System; Auszubildender; Ausbildungsabbruch; Berufseinmündung; Zweite Schwelle; Schweiz